Sclero-Hyalinized Low-Grade Appendiceal Mucinous Neoplasm Clinically Mimicking an Ovarian Mass - Nnaemeka Thaddeus Onyishi; Anthony Jude Edeh; Ngozi Regina Dim (Case Reports in Pathology)
Low-grade appendiceal mucinous neoplasm is a tumor of the appendix whose major clinical relevance derives from its inherent potential for peritoneal dissemination as pseudomyxoma peritonei. It sometimes poses challenges in clinical, radiological, and pathological diagnosis, and it may be confused with gynecological conditions in females. We report a case of low-grade appendiceal mucinous neoplasm presenting as firm sclerotic cystic mass and was initially suspected to be an ovarian mass in a postmenopausal woman. We review the literature for the pathogenesis and clinical implication of sclerohyalinization in mucinous appendiceal tumors.